Spatial variability of soil and leaf nutrient contents in basal stem rot disease infected oil palm areas - Muhamad Tajudin, Nur Shuhada (2015)
The basal stem rot (BSR) disease caused by fungi Ganoderma had been reported as the most destructive disease of oil palm in Southeast Asia. Adequate contents of nutrient in soil and leaf are necessary to improve the crop yields, plant health and its productivity. This study focus on the applications of geographic information system (GIS) tools to observe the occurrence of the BSR disease, spatial distributions of nutrients in the soil and leaf and to determine their relationship with the disease. The study was conducted in four different blocks, representing two different ages of oil palm. The BSR disease distributions in the study sites were observed from 2009 - 2012 by ground census in combinations with soil and leaf samplings. The BSR disease had increased and spread rapidly in mature oil palm plantation compared to young palm. By 2012, more than 40% of areas in mature oil palm plantations were dominated by high to very high categories of infected area. In the same year, less than 1% of area in young palm blocks was classified into very high category of infected area. For the soil and leaf nutrients determination, soil and leaf were collected based on two level of disease severity in 2009, 2010 and 2011 and by grid sampling in 2012. Content of soil nutrient in T0 and T1 did not show any significant trend between two levels of severity within the three years, while almost all nutrients in the leaf showed a higher value of nutrients in T0 compared to T1, especially in the year of 2010 (p<0.05). A significant reduction (p<0.05) of nutrients in T1 leaves were observed temporally, as higher content of nutrients recorded in 2009 and the lowest in 2011. From the spatial distributions in 2012, N and P content in soil were classified as high in all of the blocks, ranged from 0.15 to 0.48% and 6.99 to 98.39%, respectively. Potassium was classified as low to moderate level with value ranged from 0.04 to 0.59%. The same trend was also found in Ca and Mg distribution, where the area of young palm blocks was dominated by very low to moderate content. Zinc showed a sufficient content in soil, ranged from low (>0.20 ppm) to moderate (>0.25 ppm), while Cu showed a moderate content (>1.60 ppm) in all of the blocks. Leaf nutrients analysis also showed a higher content of N and P, ranged from 1.99 to 4.38% and 0.11 to 0.56%, respectively. Distributions of K, Ca, Mg and Cu from the leaf collected was considered as deficient in all of the blocks with value lower than optimum level. Correlation analysis between BSR disease and nutrient content indicated that, N in both soil and leaf showed a significantly positive relationship (p< 0.01) with the disease ranged from low to moderate strength of relationship. Nevertheless, Ca showed a significantly negative correlation (p<0.01 and <0.05) with only weak relationship. This suggests that, the BSR disease occurrence may be influenced by the unbalanced nutrient factors observed in this study area. The ability of GIS tools for determining spatial and temporal distributions of disease and nutrients is useful in making monitoring studies and management decisions especially in large plantation areas.